Direct synthesis of formic acid via CO2 hydrogenation over Cu/ZnO/Al2O3 catalyst. (20th January 2018) - Chiang, Chao-Lung; Lin, Kuen-Song; Chuang, Hui-Wen
Abstract: Cu/ZnO/Al2 O3 catalysts were prepared by co-precipitation of copper, zinc, and aluminum nitrate hydrates (Cu: Zn: Al = 5:3:2, molar ratio) with 1 M NaHCO3 aqueous solution at several calcination temperatures (300, 400, and 500 °C) in air stream, and then reduced in H2 -containing stream for 2 h. Crystal structures and particle morphologies of 300/400/500 °C-calcined Cu/ZnO/Al2 O3 catalysts were thoroughly investigated. Shifts of pore textural properties and surface chemical compositions between fresh and used Cu/ZnO/Al2 O3 were respectively observed using nitrogen isotherms and XPS spectra. Strengths of acidic and basic active sites over calcined Cu/ZnO/Al2 O3 were measured with NH3 and CO2 –TPD curves. Furthermore, the Cu/ZnO/Al2 O3 calcined at 300 °C owned the largest dispersion of active copper (DCu  = 53.90%) and maximum degree of reduction (Rmax  = 60.8%), which is more favorable for HCOOH and CH3 OH formations. Notably, the EXAFS spectra showed that the Cu species in catalysts have a CuO bonding with bond distances of 1.93–1.96 Å and coordination numbers of 2.25–2.47, respectively. It revealed that Cu atoms over Cu/ZnO/Al2 O3 calcined at lower temperature have more unoccupied binding sites for HCOOH and CH3 OH formations. In terms of catalytic performances, the highest CO2 conversion (13.1%), HCOOH selectivity (59.6%), HCOOH yield (7.6%), TON value (6.17), and TOF value (2.06) were gained at 140 °C and 30 bar in 5 h, respectively. The durability of Cu/ZnO/Al2 O3 was 22 h in a 24-h measurement at 140 °C and 30 bar. The optimal rate constant (2.28 × 10 −2 min −1 ) and activation energy (21.4 kJ mol −1 ) of HCOOH formation were respectively evaluated by pseudo first-order model and Arrhenius equation with good fitting. A mechanism was also proposed for HCOOH and CH3 OH formations in the cyclic CO2 hydrogenation. Graphical abstract: Image 1 Highlights: Cu/ZnO/Al2 O3 prepared with co-precipitation process was investigated. Cu/ZnO/Al2 O3 with active sites was calcined with an air-H2 stream at 300 °C. High catalytic performances of Cu/ZnO/Al2 O3 were obtained at 140 °C and 30 bar. The durability of as-synthesized Cu/ZnO/Al2 O3 was confirmed as 22 h. A reasonable mechanism of HCOOH/CH3 OH formation by CO2 hydrogenation was proposed.